P11.11 Circulating Pro-Angiogenic Cells and Proteins in Patients with Glioma and Acute Myocardial Infarction: Differences in Neovascularization between Neoplasia and Tissue Regeneration. (6th September 2019) - Huizer, K; Sacchetti, A; Dik, W; Kros, J M; Mustafa, D
Abstract: BACKGROUND: Although extensive angiogenesis takes place in glial tumors, anti-angiogenic therapies have remained without the expected success. In the peripheral circulation of glioma patients increased numbers of endothelial precursor cells (EPCs) are present, potentially offering targets for anti-angiogenic therapy (Zheng et al., Ann Neurol, 2007). However, for an anti-angiogenic therapy to be successful, the therapy should specifically target glioma-related EPC subsets and secreted factors. Here we compared the EPC subsets and plasma factors in the peripheral circulation of patients with gliomas to acute myocardial infarctions (representing fysiologic regeneration). MATERIAL AND METHODS: We investigated the five most important EPC subsets and 21 angiogenesis-related plasma factors in peripheral blood samples of 29 patients with glioma, 14 patients with myocardial infarction and 20 healthy people as controls, by an advanced FACS protocol (Huizer et al., PlosOne 2018) and Luminex assay. RESULTS: In GBM patients all EPC subsets were elevated as compared to healthy subjects. In addition, HPC and KDR + cell fractions were higher than in MI, while CD133 + and KDR + CD133 + cell fractions were lower. There were differences in relative EPC fractions between the groups: KDR + cells were the largest fraction in GBM while CD133 + cells were the largest fraction in MI. An increase in glioma malignancy grade coincided with an increase in the KDR + fraction while the CD133 + cell fraction decreased relatively. Most plasma angiogenic factors were higher in GBM than MI patients. In both MI and GBM, the ratio of CD133 + HPCs correlated significantly with elevated levels of MMP9. In the GBM patients MMP9 correlated strongly with levels of all HPCs. CONCLUSION: In conclusion, the data demonstrate that EPC traffic in patients with glioma is different from that in normal tissue regeneration. Therefore, the effects of glioma extent beyond the brain, and future therapies aimed at lowering KDR + cells and HPCs may add to effective treatment.